2021
DOI: 10.1002/vetr.1081
|View full text |Cite
|
Sign up to set email alerts
|

Information sourcing by dog owners in the UK: Resource selection and perceptions of knowledge

Abstract: Background: Dogs are a popular pet in the UK. Information resources utilised by dog owners can influence welfare at acquisition and throughout a dog's lifetime. This study determined where UK dog owners source information, and how perceptions relating to pedigree dog breeding and health may influence this process. Methods: This cross-sectional study used online questionnaires to explore the information resources used by dog owners and their perceptions of veterinary surgeons' and dog breeders' knowledge. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The current study also identified friends or family as an important reported influence in the decision to get a dog. This is in line with findings from previous research that highlight the influential role friends or family may play in acquisition decisions, for instance as a common source of pre-acquisition information, as well as influencing decisions around breed choice ( 11 , 61 ). Understanding the nuances of discussions between potential dog owners and their family and friends would be a worthwhile aim of future research which may enable the development of more targeted interventions to promote responsible decision-making around dog acquisition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study also identified friends or family as an important reported influence in the decision to get a dog. This is in line with findings from previous research that highlight the influential role friends or family may play in acquisition decisions, for instance as a common source of pre-acquisition information, as well as influencing decisions around breed choice ( 11 , 61 ). Understanding the nuances of discussions between potential dog owners and their family and friends would be a worthwhile aim of future research which may enable the development of more targeted interventions to promote responsible decision-making around dog acquisition.…”
Section: Discussionsupporting
confidence: 91%
“…Previous evidence suggests that although almost half of UK pet owners (45%) would be interested in a pre-acquisition consultation with a veterinarian, only 3% had already had one ( 67 ). To maximize potential impact, future interventions developed to achieve this aim could usefully consider the other information sources people commonly use prior to acquisition, which include websites, books, and friends and family ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kuhl and colleagues' data, gathered in 2013, show that internet sources were owners' preferred route to accessing canine health and welfare information. 10 This finding is corroborated by a more recent review article describing factors affecting the decision making of prospective pet dog owners, which highlighted the importance of the internet as a source of information. 11 Similarly, a survey conducted with UK-based dog owners and prospective owners in 2019 confirmed that owners most commonly consulted online sources of information before acquiring a dog.…”
Section: What You Need To Knowmentioning
confidence: 78%
“…In a study summarised on p 415 of this issue of Vet Record, Kuhl and colleagues investigated how prospective dog owners source information relating to acquiring a dog and how their pre-existing perceptions of the knowledge of various stakeholders (eg, vets and breeders) may influence this information-seeking behaviour. 10 Their findings provide insight into aspects of both capability, in the form of knowledge, and opportunity, in terms of the sourcing/routes of access to that knowledge.…”
Section: What You Need To Knowmentioning
confidence: 99%
See 1 more Smart Citation